Randomized Trial of Platelet-Transfusion Thresholds in Neonates - Curley, Anna; Stanworth, Simon J; Willoughby, Karen; Fustolo-Gunnink, Susanna F; Venkatesh, Vidheya; Hudson, Cara; Deary, Alison; Hodge, Renate; Hopkins, Valerie; Lopez Santamaria, Beatriz; Mora, Ana; Llewelyn, Charlotte; et al. (The New England journal of medicine, 2019)
The rate of death or major bleeding was significantly higher among preterm infants with severe thrombocytopenia assigned to transfusions at higher platelet-count thresholds (50,000 per cubic millimeter) than among those assigned to lower thresholds (25,000 per cubic millimeter).